Intersectoral coordination between health and agriculture : zoonoses, food safety and foot-and-mouth disease : final report and proceedings (PAHO Washington, D.CUS, 2002)
Analyses and evaluates the progress made by the countries in veterinary public health and animal health with the cooperation of PAHO. Promotes intersectoral action between health and agriculture for the prevention, control and eradication of zoonoses and other socially and economically important animal diseases, as well as foodborne diseases.
Keywords: ANIMAL DISEASES